The effect of value proposition on purchase intention of clothing products at PT Vendor Indonesia (Lighthouse Publishing, 2023)
A company will compete to provide the best service to its consumers, starting from the value offered to the quality of the products that consumers will use. Each company has its own characteristics in offering its value proposition to consumers, one of which is carried out by PT Vendor Indonesia. Before offering its products to consumers, PT Vendor Indonesia has analyzed the market first, regarding the consumer experience in using convection, they said that when using convection services for clothing needs such as making t-shirts, jackets, airy shirts, and others, several times encountered problems in terms of poor product quality, order incongruities, irresponsible convection, improper project creation time, and other issues of previous convection they've used. This study aims to determine the effect of value proposition on consumer purchasing intention on the convection of PT Vendor Indonesia. Purchase intention is an action in the form of a desire or desire and is carried out before making the purchase process. The value proposition is to create each different consumer segment by connecting the essential elements that each segment needs. The samples used in this study were students who knew the convection of PT Vendor Indonesia or who had made purchases on the convection of PT Vendor Indonesia, with a total of 160 respondents. This sample uses a purposive sampling technique with the SPSS 26 multiple linear regression method. The results showed that the value proposition variables consisting of functional value, economic value, emotional value, and symbolic value have a significant influence on consumer purchase intentions, meaning that the value of consumer value offered affects the high and low product purchase intention at PT Vendor Indonesia.